The rise of independent female protagonists: a research on the animated films Putih (2001) and Kring! (2019) / Sharifah Nur Sabrina Syed Abdul Hamid and Mohamed Razeef Abdul Razak - Syed Abdul Hamid, Sharifah Nur Sabrina; Abdul Razak, Mohamed Razeef (Faculty of Art and Design, 2023)
Representation is significant especially in media driven society nowadays. We incidentally and unknowingly construct our opinions and thoughts through the consumption of varieties of different types of media, but one of the most powerful tools to communicate and share ideas with audiences is through moving pictures, especially since the boom of the creative and digital industries. That media would be animation. Independent animated films in Malaysia are expanding although slowly but at a steady pace. More and more audiences of different generations are able to tune in as digital media consumption is much easier to access. This helps audiences to appreciate the value of positive messages these films attempt to convey. Both Kring! (2019) and Putih (2001) hold deep sentimental values as both short films, even though small, depict certain aspects of personality traits, in line with the concept of feminism itself. Although both are in stark contrast with each other, both of the females depicted clearly how women are mirrored and perceived in the current society and era when they are created. It is crucial to see the progress and the significant growth of how women are portrayed on screen, although looked very unimportant, but one of the stepping stones in holding women’s virtue as an abled human being, functioning in society.